2018
DOI: 10.1002/ajim.22936
|View full text |Cite
|
Sign up to set email alerts
|

Finding causation in occupational fatalities: A latent class analysis

Abstract: BackgroundThe method “Learning by mistakes” was developed in Italy to conduct occupational injury investigations and to collect information on the genesis of injuries. The aim is to analyze data classified with this method in order to identify patterns among the factors contributing to injury dynamics.MethodsData regarding 673 factors, corresponding to 354 occupational fatalities that occurred in the Piedmont region (north‐west of Italy) during 2005‐2014 were considered. Latent Class Analysis (LCA) was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The authors selected the eight-class model. In their study, most of the factors fell in the class “fall from height or vehicle rollover due to incorrect practice 18 . Although the number of classes was different in the mentioned studies in comparison to our findings, however, inconsistent with other studies our study demonstrated that some workers fell under catastrophic class with a high probability of death.…”
Section: Resultsmentioning
confidence: 99%
“…The authors selected the eight-class model. In their study, most of the factors fell in the class “fall from height or vehicle rollover due to incorrect practice 18 . Although the number of classes was different in the mentioned studies in comparison to our findings, however, inconsistent with other studies our study demonstrated that some workers fell under catastrophic class with a high probability of death.…”
Section: Resultsmentioning
confidence: 99%